7 seconds - Youssou N'dour; Neneh Cherry; EMI Virgin Music Publishing; Sony Music Entertainment (France : EMI Virgin Music Publishing, 1994)
Contains four different mixes of the song 7 Seconds and an additional track.
CD 1 : Album version / (5:04) -- New old mix / (5:43) -- Hip Hop 1 mix / (6:25) -- Dub mix / (6:08) -- Mame Bamba / (4:57).
Koleksi Khas Wiramanja.
Keywords: Songs, English